Shopping styles and preferences among local and international tourists in Kuala Lumpur / Anis Liyana Buliah - Buliah, Anis Liyana (2016)
Shopping is one of the tourist's favourite activities and has become a significant economic contributor to the tourism and retail industry. Tourist tends to look for souvenir and purchase it as a symbol and memory of their vacation or trip. However, souvenir is no longer the primary product that tourist purchases. Therefore, the aim of this study is to examine the interrelationship between tourist shopping preferences, tourist demographic, and tourist shopping styles during their visit to Kuala Lumpur. This study adapts quantitative data collection method, whereby 471 tourists had participated. Administrative questionnaires were distributed personally and the mall intercept surveys had been used to conduct this study. The data was analyzed by using the Statistical Program for the Social Science (SPSS) to answer the research objectives and research questions. The findings revealed that there is significant relationship between demographic characteristics and tourist preferences towards tourist's shopping style. Both local and international tourists prefer to buy clothing while they are in Kuala Lumpur. In terms of their shopping styles, the international tourists tend to be Novelty-seeking and local tourists tend to be Price Conscious, "Value for Money" during their shopping. The study concludes that understanding the tourist shopping styles according to their preferences and demographic characteristics is beneficial for tourism and retail industry.